(untitled) (Al-Aasar, 2025)
Youth are the moral foundation and dynamic force of every society. They represent the future of every society and play an important role in its growth and development. Their intellectual, moral, and social development is very important because they drive social changes and progress. This research paper explores how young people can be taught good behaviour based on the teachings of the Prophet Muhammad (PBUH). Training youth in the light of Prophetic teachings is a process that cultivates virtuous character, responsible citizenship, social effectiveness, and respect for human rights and tolerance. It explains how the Prophet’s moral teachings and practical examples serve as a comprehensive framework for developing ethical awareness, social responsibility, and constructive engagement among youth. This study focuses on important qualities like honesty, kindness, responsibility, humanity, and respect for others can help to build a balanced and responsible character and society. It also discusses how these values are still important in contemporary world, especially when many young people face moral and ethical problems and social issues. Using a qualitative research method and referring to Qur’anic verses and Hadiths, the findings reveal that the Prophet’s (PBUH) teachings and ethical system offers a timeless framework to raise socially aware, morally good, and community-oriented youth.